1997
DOI: 10.1109/10.554766
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity distributions of EEG and MEG measurements

Abstract: It is generally believed that because the skull has low conductivity to electric current but is transparent to magnetic fields, the measurement sensitivity of the magnetoencephalography (MEG) in the brain region should be more concentrated than that of the electroencephalography (EEG). It is also believed that the information recorded by these techniques is very different. If this were indeed the case, it might be possible to justify the cost of MEG instrumentation which is at least 25 times higher than that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(76 citation statements)
references
References 13 publications
3
73
0
Order By: Relevance
“…The temporal resolution of EEG is identical to that of MEG, and both are superior to hemodynamic measures by two orders of magnitude (milliseconds vs. seconds). Whether MEG confers advantages in spatial resolution over the EEG is now a matter ofdebate (Cohen et al, 1990;Malmivuo, Suihko, & Eskola, 1997;Wikswo et al, 1993). Coupled with advances in electrical source localization, dense sensor array EEG may be the most cost-effective approach to neuroimaging now available, adding critical anatomical context to the rich temporal information of scalp electrical recordings.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…The temporal resolution of EEG is identical to that of MEG, and both are superior to hemodynamic measures by two orders of magnitude (milliseconds vs. seconds). Whether MEG confers advantages in spatial resolution over the EEG is now a matter ofdebate (Cohen et al, 1990;Malmivuo, Suihko, & Eskola, 1997;Wikswo et al, 1993). Coupled with advances in electrical source localization, dense sensor array EEG may be the most cost-effective approach to neuroimaging now available, adding critical anatomical context to the rich temporal information of scalp electrical recordings.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Even the modeling studies, however, have been equivocal. Some modeling work found MEG to be more accurate than EEG [Murro et al, 1995;Stok, 1987], whereas others found EEG and MEG accuracy to be comparable [Malmivuo et al, 1997], or EEG accuracy better than MEG [Mosher et al, 1993;Pascual-Marqui and Biscay-Lirio, 1993].…”
Section: Introductionmentioning
confidence: 99%
“…The earlier results with relative skull resistivities of 1/80/1 and 1/100/1 are also given. The results are thus comparable with those of our earlier paper [3]. …”
supporting
confidence: 82%